Do Sectoral Growth Promote CO2 Emissions in Pakistan? Time Series Analysis in Presence of Structural Break - Ali, Amjad; Audi, Marc; Senturk, Ismail; Roussel, Yannick (International Journal of Energy Economics and Policy, 2022)
This study has examined the impact of sectoral growth on CO2 emissions in the case of Pakistan from 1970 to 2019. ADF and PP unit root tests have been applied to check the stationarity of the data series, whereas the Zivot-Andrew structural break unit root test has been applied to check the existence of structural break. The results of the unit root test show there is mixed order of integration among the selected variables, Zivot-Andrew unit root test also highlights the point of a structural break in the data series. The autoregressive distributed lag model has been applied for checking the cointegration among the variables of the model. The results show that industrial growth, population density, and time trend are positively and significantly contributing to CO2 emissions in Pakistan. Whereas services sector growth is responsible for reducing CO2 emissions in Pakistan. The results show that agricultural growth and globalization are reducing CO2 emissions but this relationship is insignificant over the selected time. In the short-run industrial growth, agricultural growth, and service sector growth are reducing the level of CO2 emissions in Pakistan. Likewise long run, trend time is promoting CO2 emissions in the short run in Pakistan. The government of Pakistan can control CO2 emissions by improvement in industrial production methods, reducing population density, and promoting services sector growth. There must be some dynamic policies are required to control the time trend impact on CO2 emission in Pakistan.